Physical Geology of Shallow Magmatic Systems Dykes, Sills and Laccoliths (Advances in Volcanology,, 2018)
This book offers a high-level summary of shallow magmatic systems (dykes, sills and laccoliths) to support geoscience master and PhD students, scientists and practicing professionals. The product of the LASI (Laccoliths and Sills conference) workshop, it comprises thematic sections written by one or more experts on the respective field. It features reviews concerning the physical properties of magma, geotectonic settings, and the structure of subvolcanic systems, as well as case studies on the best-known systems. The book provides readers a broad and comprehensive understanding of the subvolcanic perspective on pluton growth, which is relevant for mineralogical processes as well as the genesis of mineral deposits.